2002
DOI: 10.1097/00006534-200208000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Breast Reconstruction with the Free TRAM or DIEP Flap: Patient Selection, Choice of Flap, and Outcome

Abstract: Recent reports of breast reconstruction with the deep inferior epigastric perforator (DIEP) flap indicate increased fat necrosis and venous congestion as compared with the free transverse rectus abdominis muscle (TRAM) flap. Although the benefits of the DIEP flap regarding the abdominal wall are well documented, its reconstructive advantage remains uncertain. The main objective of this study was to address selection criteria for the free TRAM and DIEP flaps on the basis of patient characteristics and vascular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
265
3
9

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 442 publications
(289 citation statements)
references
References 34 publications
7
265
3
9
Order By: Relevance
“…Earlier in the study period, autologous flaps were the most widely used. However, over time, implant‐based reconstructions have become more common3 7, 22 34, 35, 36. This may be explained by implant reconstructions requiring less complicated operations and shorter operating times, lack of donor‐site morbidity and no requirement for microvascular surgery expertise as in the case of some autologous procedures (DIEP flaps).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier in the study period, autologous flaps were the most widely used. However, over time, implant‐based reconstructions have become more common3 7, 22 34, 35, 36. This may be explained by implant reconstructions requiring less complicated operations and shorter operating times, lack of donor‐site morbidity and no requirement for microvascular surgery expertise as in the case of some autologous procedures (DIEP flaps).…”
Section: Discussionmentioning
confidence: 99%
“…This may be explained by implant reconstructions requiring less complicated operations and shorter operating times, lack of donor‐site morbidity and no requirement for microvascular surgery expertise as in the case of some autologous procedures (DIEP flaps). Complex patient selection and the requirement for preoperative CT (in DIEP flap surgery) also make autologous reconstructions a less attractive reconstructive technique35, 36, 37. ADMs were first reported in 200538.…”
Section: Discussionmentioning
confidence: 99%
“…In the new millennium, we have resurrected the anatomy phase with the development of perforator flaps. The development of the DIEP followed by SGAP and subsequent perforator flaps has created a new phase of microsurgery [2,[13][14][15][16][17]. The next phase would seem to be poised for that of allotransplantation [18].…”
Section: Introductionmentioning
confidence: 99%
“…[2] Other large series have reported similar results with respect to major complications. [2][3][4][5][6][7]13,16] With regards to vascular problems, venous congestion tends to be the primary concern for microsurgeons who perform DIEP flap breast reconstruction. Complications due to the venous drainage or venous anastomosis have been shown to be eight times more common than issues arising from arterial insufficiency or arterial anastomotic complications.…”
Section: Introductionmentioning
confidence: 99%
“…[2] These problems can lead not only to the rare total flap failure but more commonly to the need to return to the operating room in the immediate postoperative period to correct venous insufficiency and even partial flap failure and fat necrosis in the long-term. [3][4][5][6][7] Anatomic studies have shown that the deep inferior epigastric vein (DIEV) connects with the superficial inferior epigastric vein (SIEV) through a system of choke vessels within the flap. [8] In numerous studies, the superficial venous system has been used to adequately decongest the flap in cases where venous congestion was clinically observed [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%